Truncated euler polynomials - Komatsu, Takao; Pita-Ruiz, Claudio (My University, 2018)
We define a truncated Euler polynomial Em,n(x) as a generalization of the classical Euler polynomial En(x). In this paper we give its some properties and relations with the hypergeometric Bernoulli polynomial. MSC 2010: Primary 11B68; Secondary 11B83, 11B37, 05A15, 05A19